TINJAUAN YURIDIS PENETAPAN HARGA (PRICE FIXING) BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT (Studi Kasus Putusan Komisi Pengawas Persaingan Usaha Nomor 03/KPPU-I/2003) - Sinabariba, Yan Weilly Parsaoran; Lestari, Rika; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The prohibition of unfair business competition in Indonesia has been formulated in a legal codification. Law Number 5 Year 1999 Concerning Monopolistic Practices and Unfair Business Competition is a law which contains the regulation of the prohibition of unfair business competition in Indonesia. One of the prohibitions contained in the law is the prohibition on pricing. The prohibition of pricing provided for in Article 5 to Article 8 in the law prohibits price fixing by agreement. The prohibition in Law No. 5 of 1999 concerning Monopolistic Practices and Unfair Business Competition itself has two concepts of approaches in the nature of the prohibition, namely per se illegal and the rule of reason. Both of these approaches are used by the Commission for the Supervision of Business Competition in deciding the behavior that is alleged to violate Anti-Monopoly Law and Unfair Business Competition. As in the case involving 7 (seven) reported shipping companies, namely: PT. Meratus Sailing (Reported I), PT. Tempuran Emas Tbk (Reported II), PT. (Persero) Djakarta Lloyd (Reported III), PT. Jayakusuma Perdana Lines (Reported IV), PT. Samudra Indonesia Tbk (Reported V), PT. Tanto Line (Reported VI), PT. Lumintu Sinar Perkasa (Reported Party VII). The case was terminated in Decision No. 03/KPPU-I /2003 by the Business Competition Supervisory Commission. The purpose of this study is to examine how the concept of approach used by the Commission Assembly Team of Business Competition Supervisors in considering the case and decide in the decision No. 03 / KPPU-I / 2003 and how the form of pricing made by the business actors who became parties reported In the case. This research will use normative research method in analyzing it. While the materials used in this study adalan materials bibliography. Keywords: KPPU Decision, Price Fixing, Unfair Business Competition